Clinical Features of Probable Cluster Headache: A Prospective, Cross-Sectional Multicenter Study - Sohn, Jong-Hee; Choi, Yun-Ju; Kim, Byung-Kun; Chung, Pil-Wook; Lee, Mi Ji; Chu, Min Kyung; Ahn, Jin-Young; Kim, Byung-Su; Song, Tae-Jin; Oh, Kyungmi; Lee, Kwang-Soo; Kim, Soo-Kyoung; et al. (Frontiers in Neurology, 2018)
Background: Epidemiological data of probable cluster headaches (CH) are scarce in the relevant literature. Here, we sought to assess the prevalence and clinical characteristics of probable CH in comparison with definite CH. Methods: Data used in this study were obtained from the Korean Cluster Headache Registry (KCHR), a prospective, cross-sectional, multicenter headache registry that collected data from consecutive patients diagnosed with CH. Results: In total, 159 patients were enrolled in this study; 20 (12.6%) were diagnosed with probable CH. The most common unfulfilled criterion in patients with probable CH was the duration of attack, which was found in 40% of patients with probable CH. Among clinical characteristics, the number of autonomic symptoms tended to be lower in probable CH than in definite CH (1.7 ± 1.2 vs. 2.4 ± 1.5, p = 0.051) and conjunctival injection and lacrimation showed an increased odds ratio (OR) [OR = 3.03; 95% confidence interval (CI): 1.03–8.33] in definite CH. The groups did not differ with regard to baseline demographic characteristics, disability, impact on life, or treatment response. Conclusions: Probable CH is relatively common among CH disorders, with a clinical impact similar to that of definite CH.